Behavioural Adaptations to Arctic Winter: Shelter Seeking by Arctic Hare (Lepus arcticus) - Gray, David R. (ARCTIC, 1993)
Behavioural modifications used by arctic hares, Lepus arcticus, to maintain their normal body temperature in late winter, including posture, orientation, the use of natural shelter, and the digging of snow dens, were studied on Ellesmere Island, N.W.T., between 1985 and 1992 and on Bathurst Island, N.W.T., between 1968 and 1992. Hares adopted a near-spherical shape while resting with only the thick pads of the hind feet touching the snow. Hares typically rested together in closely spaced winter groups of up to 28 hares. Huddling did not occur, except in young littermates in summer. Hares in groups did not usually seek shelter, but solitary hares normally groomed, rested, and reingested in the shelter of large rocks. When wind speeds dropped below 10 km/h, resting hares shifted from facing away from wind to an orientation towards the sun. As daily mean temperatures increased in April-May, the usual resting posture changed from the tightly curled resting sphere to crouching and sprawling. Hares used natural shelter, especially rocks and snowdrifts, and man-made structures. They also modified snowdrifts by digging snow dens up to 188 cm in length. Thirty-seven dens were seen in 8 of 15 years of observations at Bathurst Island, and seven were seen on Ellesmere Island in 1 of 5 seasons. Snow dens were not used for feeding and their value as safety from predators is likely secondary to their value as shelter.Key words: arctic hare, shelter seeking, sheltering, winter adaptations, posture Cette étude, qui s'est déroulée entre 1985 et 1992 dans l'île d'Ellesmere (T.N.-O.) et entre 1968 et 1992 dans l'île Bathurst (T.N.-O.), porte sur les modifications du comportement qu'affiche le lièvre arctique, Lepus arcticus, afin de maintenir sa température corporelle normale à la fin de l'hiver. Ces modifications comprenaient la position et l'orientation du corps, l'utilisation d'un abri naturel et le creusement de gîtes dans la neige. Les lièvres prenaient une position presque sphérique au repos, seuls les épais coussinets de ...